Eigenstrain reconstruction of residual strains in an additively manufactured and shot peened nickel superalloy compressor blade - Salvati, E; Lunt, A; Ying, S; Sui, T; Zhang, H; Heason, C; Baxter, G; Korsunsky, A (Elsevier, 2017)
Numerical modelling of the residual stresses and strains within mechanical components is of great importance for improving the quality and reliability of design for structural integrity. A particularly versatile and powerful approach is offered by direct and inverse eigenstrain modelling. The nature of the eigenstrain modelling approach is that it not only generates an efficient parametric representation of the residual stress field, but also ensures consistency by enforcing stress equilibrium and strain compatibility. In the present study we propose a particular way of prescribing the eigenstrain field due to surface treatment such as shot peening. Eigenstrain variation is described by a continuous function of the distance from the boundary of the object in a two-dimensional model of its cross-section. The procedure is compatible with the use of commercial numerical simulation software, and allows correct assignment of all eigenstrain components. We apply the technique to the evaluation of residual strain within an add itively manufactured nickel superalloy compressor blade that was subsequently subjected to shot peening treatment. Two experimental techniques are used to validate the model, namely, Focused Ion Beam ring core milling (FIB-DIC) and synchrotron X-ray Powder Diffraction (SXRPD). Consistency between model prediction and experimental measurements provides verification of the suitability of eigenstrain modelling as consistent basis for the incorporation of residual stress effects on the deformation behaviour of manufactured components.